An ester derivative of tenacigenin B from Marsdenia tenacissima (Roxb.) Wight et Arn reversed paclitaxel-induced MDR in vitro and in vivo by inhibiting both P-gp and MRP2. (10th August 2022) - Wu, Zhou-Li; Chen, Yan; Qu, Zhao; Wu, Gui-Yun; He, Xiao-Feng; Huang, Jia-Wen; Meng, Qi-Qi; Hu, Yuan-Hao; Shen, Xiao-Ling; Yang, Rui-Yi; Hu, Ying-Jie
Abstract: Ethnopharmacological relevance: Marsdenia tenacissima is a medicinal plant, used as a raw material for cancer treatment in China. In our previous studies, 11α- O -2-methylbutanoyl-12β- O -tigloyl-tenacigenin B (MT2), the main steroid aglycone isolated from M. tenacissima, was found to significantly enhance the antitumor activity of paclitaxel (PTX) in vivo . However, it is unclear whether MT2 reverses multidrug resistance (MDR) in tumors. Aim of the study: To determine the role and mechanism of MT2 in reversing tumor MDR. Materials and methods: MDR cell line HeLa/Tax was established from the human cervical carcinoma cell line HeLa by long-term exposure to subtoxic concentrations of PTX and was used to evaluate the ability of MT2 to restore chemosensitivity of cells both in vitro and in a nude mouse model. The expression of P-glycoprotein (P-gp) and multidrug resistance-associated protein 2 (MRP2) was determined using western blotting and immunohistochemistry. The substrate transport function was assessed using an MDR function assay kit. The binding modes of MT2 and P-gp were determined using the conformation-sensitive anti-P-gp antibodies. The permeability and transport properties of MT2 were analyzed in Caco-2 cell monolayers. Results: Compared to parental cells, HeLa/Tax cells overexpress P-gp and MRP2 and are approximately 100–360 fold more resistant to the anticancer drugs PTX, docetaxel, and vinblastine. MT2 at 5 or 10 μmol/L significantly increased the sensitivity of HeLa/Tax to these three anticancer drugs (18–56-fold decrease in IC50 value) and suppressed the expression of P-gp and MRP2. Knockdown of P-gp with small interfering RNA partially reversed MT2-induced sensitivity to PTX in HeLa/Tax cells. Moreover, MT2 directly inhibited P-gp-mediated substrate transport while interacting with membrane P-gp in non-substrate ways. MT2 was highly permeable and could not be transported in the Caco-2 cell monolayers. In nude mice bearing HeLa/Tax xenografts, the combination treatment with MT2 and PTX exerted a synergistic inhibitory effect on the growth of tumors and the expression of P-gp and MRP2 without increasing toxicity. Conclusion: MT2 is a potential agent for reversing MDR. It impedes membrane drug efflux pumps by suppressing P-gp and MRP2 expression, and directly inhibiting the transport function of P-gp. Graphical abstract: Image 1 Highlights: MT2 sharply reversed paclitaxel-induced MDR in both HeLa cells and xenografts. MT2 suppressed the expression of MDR proteins P-gp and MRP2 in vitro and in vivo. MT2 inhibited P-gp mediated substrate transport in a non-substrate way.